Direct Ink Writing of Anisotropic Luminescent Materials - Mattia Sabadin; Jeroen A. H. P. Sol; Michael G. Debije (Crystals, 2022)
Luminescent solar concentrators are relatively inexpensive devices proposed to collect, convert, and redirect incident (sun)light for a variety of potential applications. In this work, dichroic dyes are embedded in a liquid crystal elastomer matrix and used as feedstock for direct ink writing. Direct ink writing is a promising and versatile application technique for arbitrarily aligning the dichroic dyes over glass and poly(methyl methacrylate) lightguide surfaces. The resulting prints display anisotropic edge emissions, and suggest usage as striking visual objects, combining localized color and intensity variations when viewed through a polarizer.